Optimalisasi Strategi Promosi Digital melalui Opencart untuk Mendongkrak Daya Saing Produk Makanan dan Hasil Bumi di Solok - Dina Hanifah, Arini; Annas, Firdaus; Difa Andini, Mawar; Rubiyanti Dewi, Rahma (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This study aims to develop a digital promotion strategy based on Opencart to enhance the competitiveness of local food products and agricultural produce in Solok. Solok, as an agrarian region with abundant potential in agricultural produce and unique food products, faces challenges in reaching wider markets due to the limitations of traditional promotion and distribution systems. A modern, technology-based promotional system is needed to support local businesses in increasing their competitiveness in the digital era. Ideally, local entrepreneurs can utilize a digital platform specifically Designed to support promotional activities efficiently, data-driven, and globally oriented. Through technological integration, it is expected that Solok's food products and agricultural produce will not only gain recognition locally but also compete in national and international markets. This research employs the Research and Development (R&D) method with the ADDIE model approach (Analysis, Design, Development, Implementation, Evaluation). The study resulted in a web-based promotional media using the Opencart application, Designed to meet the promotional needs of local businesses. This media has been proven valid, practical, and effective in enhancing the efficiency of digital promotion. Equipped with features such as product personalization, automated discount systems, and social media integration, the platform significantly improves sales while expanding market reach beyond the region. User evaluations revealed high satisfaction levels with the platform's ease of use, particularly in its real-time sales reporting feature. In conclusion, the Opencart-based promotional media not only enhances the competitiveness of local food products and agricultural produce in Solok but also holds great potential for implementation in other agrarian regions with similar characteristics.